Viruses, IRESs, and a universal translation initiation mechanism. Issue 1 (2nd January 2018) - Roberts, Luc; Wieden, Hans-Joachim
Abstract: Internal ribosome entry sites (IRESs) are cis-acting RNA elements capable of recruiting ribosomes and initiating translation on an internal portion of an mRNA. This is divergent from canonical eukaryotic translation initiation, where the 5' cap is recognized by initiation factors (IFs) that recruit the ribosome to initiate translation of the encoded peptide. All known IRESs are capable of initiating translation in a cap-independent manner, and are therefore not constrained by the absence or presence of a 5' m 7 G cap. In addition to being cap-independent, IRES-mediated translation often uses only a subset of IFs allowing them to function independently of canonical initiation. The ability to function independently of the canonical translation initiation pathway allows IRESs to mediate gene expression when cap-dependent translation has been inhibited. Recent reports of viral IRESs capable of initiating translation across taxonomic domains (Eukarya and Bacteria) have sparked interest in designing gene expression systems compatible with multiple organisms. The ability to drive translation independent of cellular context using a common mechanism would have a wide range of applications ranging from agriculture biotechnology to the development of antiviral drugs. Here we discuss IRES-mediated translation and critically compare the available mechanistic and structural information. A particular focus will be on IRES-meditated translation across domains of life (viral and cellular IRESs), IRES bioengineering and the possibility of an evolutionary conserved translation initiation mechanism.